(untitled) (Indian Journal of Animal Production and Management, 2014)
A study was carried out in the AMUL milk shed area on 30 postpartum crossbred cows, comprising 20 true anoestrus and 10 normal cyclic cows to evaluate clinical response to oestrus induction protocols and plasma progesterone and biochemical profile at different time intervals post treatment/pot-AI. The oestrus induction response obtained with CIDR and Ovsynch protocol in anoestrus cows (10 each) was 100% and 90% with oestrus induction intervals of 6.00 + 3.22 and 86.67 + 3.33 hrs from PG injection, respectively. The conception rates at induced/first oestrus and overall of 3 cycles were 50 and 80% in CIDR 30 and 60% in Ovsynch protocol: and 80% in normal cyclic control cows. The plasma progesterone levels in CIDR protocol on day 0, 7, 9/10 (AI) and day 21 post-AI were 0.65+0.23, 3.48+0.54, 0.48+0.13 and 10.44+1.77ng/ml in conceived and 0.70+0.18, 3.61+1.05, 0.32+0.09 and 1.42+0.38 ng/ml in non conceived cows. The corresponding P4 levels in Ovsynch protocol were 0.28+0.06, 2.98+0.93, 0.48+0.19 and 8.06+1.16 ng/ml in conceived and 0.32+0.07, 3.82+1.35, 0.52+0.30 and 1.24+0.71 ng/ml in non-conceived cows. There was significant cariation in P4 profile between periods in both the protocols (P<0.05). The P4 levels in conceived and non-conceived cows of normal cyclic control group on day 0(AI) were 0.24+0.04 and 0.41+0.15ng/ml, and on day 21 post-AI 10.48+1.34 nd 0.63+0.11 ng/ml (P<0.01), respectively. The plasma total cholestrol and total protein concentrations in conceived and non-conceived cows of CIDR protocol were 173.62+13.28 and 186.43+8.94 mg/dl, and 12.59+0.38 and 11.07+0.06 g/dl, respectively, without significant variation between sampling days. In Ovsynch protocol, the corresponding calues of cholestrol and protein were 128.88+3.74 and 213.11+5.73 mg/dl, and 11.83+0.22 and 12.14+0.13 gdl. The plasma total cholestrol levels varied significantly between sampling days in non-conceived animals (P<0.05). There was significant variation between conceoved and non-conceived animals in total cholestrol profile inCIDR protocol and in total proterin in Ovsynch protocol (P<0.01). In normal cyclic control animals, the choestrol concentrations on day of AI and day 21 post-AI were 219.47+22.15 and 192.80+16.79 mg/dl and total protein levels 12.35+0.36 and 12.76+0.15 g/dl without significant variation (P0.05) between days and between pregnancy status. It is concluded that both the treatment protocols induce fertile/ovulatory oestrus and improve conception rates and plasma P4 profile in true anoestrus cows, though there was no significant infuence on plasma protein and cholestrol profile.